Potential Achilles heels of SARS-CoV-2 are best displayed by the base order-dependent component of RNA folding energy. (October 2021) - Zhang, Chiyu; Forsdyke, Donald R.
Abstract: The base order-dependent component of folding energy has revealed a highly conserved region in HIV-1 genomes that associates with RNA structure. This corresponds to a packaging signal that is recognized by the nucleocapsid domain of the Gag polyprotein. Long viewed as a potential HIV-1 "Achilles heel, " the signal can be targeted by a new antiviral compound. Although SARS-CoV-2 differs in many respects from HIV-1, the same technology displays regions with a high base order-dependent folding energy component, which are also highly conserved. This indicates structural invariance (SI) sustained by natural selection. While the regions are often also protein-encoding (e. g. NSP3, ORF3a), we suggest that their nucleic acid level functions can be considered potential "Achilles heels" for SARS-CoV-2, perhaps susceptible to therapies like those envisaged for AIDS. The ribosomal frameshifting element scored well, but higher SI scores were obtained in other regions, including those encoding NSP13 and the nucleocapsid (N) protein. Graphical Abstract: ga1 Highlights: A potential HIV genome vulnerability identified 25 years ago is now receiving attention. The same structure identification technology is here applied to the SARS-CoV-2 genome. Base order and base composition dependent folding components are distinguished. Eliminating the genome-wide influence of base composition favors local focus. Several potential SARS-CoV-2 genome structural vulnerabilities are identified.